2023
DOI: 10.3389/fmats.2023.1153421
|View full text |Cite
|
Sign up to set email alerts
|

Reliable machine learning for the shear strength of beams strengthened using externally bonded FRP jackets

Abstract: All over the world, shear strengthening of reinforced concrete elements using external fiber-reinforced polymer jackets could be used to improve building sustainability. However, reports issued by the American Concrete Institute called for heavy scrutiny before actual field implementation. The very limited number of proposed shear equations lacks reliability and accuracy. Thus, further investigation in this area is needed. In addition, machine-learning techniques are being implemented successfully to develop s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
1
0
Order By: Relevance
“…Based on an extensive dataset of 304 experiments, the results demonstrated that the TGAN technique yielded superior accuracy in comparison with existing design codes, with an R 2 of 0.96. Most recently, an ANN model was developed for the shear strength prediction of RC beams strengthened with EB-FRP jackets [37,38]. Based on extensive datasets collected covering a wide range of parameters, the ANN model had high prediction accuracy, confirming the potential of employing the ML technique in the development of current design codes.…”
Section: Shear Strengthmentioning
confidence: 87%
See 1 more Smart Citation
“…Based on an extensive dataset of 304 experiments, the results demonstrated that the TGAN technique yielded superior accuracy in comparison with existing design codes, with an R 2 of 0.96. Most recently, an ANN model was developed for the shear strength prediction of RC beams strengthened with EB-FRP jackets [37,38]. Based on extensive datasets collected covering a wide range of parameters, the ANN model had high prediction accuracy, confirming the potential of employing the ML technique in the development of current design codes.…”
Section: Shear Strengthmentioning
confidence: 87%
“…The shear capacity of RC beams was predicted mathematically using a variety of ML approaches [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42]. The use of the well-known artificial neural network (ANN) technique was adopted to investigate the impact of various crucial variables on the shear strength of FRP-RC beams [25].…”
Section: Shear Strengthmentioning
confidence: 99%
“…Based on the equilibrium of forces in a cross-section of a beam at failure, Pellegrino and Moderna [14] have obtained a theoretical equation for effective FRP strain. Nehdi et al [15], [16], and Kara [17] have taken a genetic algorithm approach whereas Hosseini and others [18], [19], [20], [21] have adopted machine learning and neural networks. Anvari et al [22] have also used an evolutionary machine learning approach, named genetic expression programming.…”
Section: Introductionmentioning
confidence: 99%